PERANAN TRANSPORTASI DALAM PARIWISATA Studi Kasus : Pemilihan Daerah Tujuan Wisata (Dtw/Destinasi) Oleh Wisatawan Di Bali - Budiartha R.M., Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011, 2012)
The rapid growth of tourism has attracted a large number of provincial and district levels in Indonesia to capture a larger portion of this economic activity. They are competing to build tourism transportation infrastructure such as ports, airports, highways and other supporting facilities in order to stimulate economic growth and an increasing number of tourists. To avoid destructive local optimatization, it is important to re-think the role of transport in ensuring the sustainability and competitiveness of Indonesian tourism. To achieve this goal, it is important to understand the reasons of people travelling to Bali and factors influencing their choice. This study identifies the factors influencing destinations choice by foreign tourists travelling to Bali and evaluates the preferences of the selected destinations. AHP Model 4 levels consisting 22 attributes on the fourth level, is proposed and tested using data collected from tourists visiting Bali. This is to determine the selection criteria of the factors that are relatively important. Using fuzzy theory and TOPSIS, the preferences of 47 destinations in Bali were ranked. The results are used to establish the priority in transport infrastructure development in relation to tourism. The study results indicate that the search for pleasure with a total escape from daily activities, personal security, friendship and / or relatives seems are the three most important factors for the tourists visiting Bali. Meanwhile, the package tourist destinations consisting Kuta, Tanah Lot, Lake and Mount Batur are primary destinations during a visit to Bali.
Keywords: Tourist Cruise, Transportation infrastructure, Tourist requirements and motivations, Destination choice, FuzzyTOPSIS.